Effect of different packaging materials on the shelf life of passion fruits during ambient and low temperature storage - Rinaldi, Maria Madalena; Dianese, Alexei de Campos; Costa, Ana Maria; Sussel, Angelo Aparecido Barbosa; Faleiro, Fabio Gelape; Junqueira, Nilton Tadeu Vilela (Journal of Postharvest Technology, 2017)
Passion fruit is generally considered to have a short storage life, because it is a very delicate, perishable fruit. The objective of this work was  to study the post-harvest conservation of Passiflora setacea fruit packed in PVC packages 12μm and 30μm thick, LDPE bags 100μm and  200μm thick, and without packaging (control), stored under ambient conditions at an average temperature of 21.3ºC and average relative  humidity of 77.8%, and in refrigerated conditions in a cold room at 10ºC and 90% relative humidity for 14 days. At the beginning of storage and  at three, seven, 10 and 14 days of storage the fruits were analyzed for titratable acidity, soluble solids, Ratio, fresh weight loss, hue angle and  post-harvest diseases. The experiment had a completely randomized design with three replicates. The 12μm PVC package, under  refrigeration, was the most efficient in the conservation of P. setacea fruit. It presented low fresh weight loss; Null percentage of fungal  infestation; soluble solids above 11% until the tenth day of storage; Titratable acid content above 2.5% throughout the experiment. Besides,  the fruit, at the end of 14 days of storage, did not show evidence of fermentation and no water condensation inside the packages.
Keywords: Passiflora setacea; storage condition; quality; physico-chemical analysis; postharvest disease